1997
DOI: 10.1359/jbmr.1997.12.11.1789
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Nitric Oxide Synthase and Cyclooxygenase Pathways in Osteoblastic MC3T3-E1 Cells

Abstract: Interleukin 1 (IL-1) and tumor necrosis factor ␣ (TNF-␣) have been implicated in the pathogenesis of osteoporosis. These proinflammatory cytokines induce both cyclooxygenase (COX) and nitric oxide synthase (NOS) with the release of prostaglandin (PG) and NO, respectively. The present study was undertaken to examine the interaction between COX and NOS pathways and their role in the regulation of osteoblastic function in MC3T3-E1 cells. Addition of IL-1␣ and TNF-␣ induced a marked increase in the production of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…In additional studies, NOS and COX, enzymes responsible for the synthesis of NO and PGE 2 , were induced by interleukin-1 (IL-1) in MC3T3-E1 cells. 46,47 In these studies it was suggested that both NO-dependent and NO-independent pathways for the production of PGE 2 exist and that the early production of PGE 2 might be independent of NO. 47 However, the stimulation of NO production by IL-1 is mediated by the inducible form of NOS (iNOS) and leads to much higher levels of NO than the stimulation by fluid flow, which runs via the constitutive form of NOS (eNOS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In additional studies, NOS and COX, enzymes responsible for the synthesis of NO and PGE 2 , were induced by interleukin-1 (IL-1) in MC3T3-E1 cells. 46,47 In these studies it was suggested that both NO-dependent and NO-independent pathways for the production of PGE 2 exist and that the early production of PGE 2 might be independent of NO. 47 However, the stimulation of NO production by IL-1 is mediated by the inducible form of NOS (iNOS) and leads to much higher levels of NO than the stimulation by fluid flow, which runs via the constitutive form of NOS (eNOS).…”
Section: Discussionmentioning
confidence: 99%
“…46,47 In these studies it was suggested that both NO-dependent and NO-independent pathways for the production of PGE 2 exist and that the early production of PGE 2 might be independent of NO. 47 However, the stimulation of NO production by IL-1 is mediated by the inducible form of NOS (iNOS) and leads to much higher levels of NO than the stimulation by fluid flow, which runs via the constitutive form of NOS (eNOS). Nevertheless, it still needs to be established whether the delayed production of PGE 2 , which has been shown to occur in response to flow as well, 8 follows the NO release pattern.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that bone cells are regulated in their activity both by circulating hormones (1) and by the interacting effects of a number of locally acting intercellular signals, including prostaglandins, growth factors, cytokines, and nitric oxide (2)(3)(4)(5)(6)(7)(8)(9). Recently, it has been reported that functional NMDA 1 -type glutamate receptors are expressed in a number of bone cell types, including rat and human osteoblasts and osteoclasts, MG-63 osteosarcoma cells, and in bone marrow megakaryocytes (10 -15).…”
mentioning
confidence: 99%
“…Park et al (22) reported that cross-talk exists between COX and NOS in head and neck cancer cell lines. There are inter- actions between COX and NOS pathways among host tissues, not only in tumor tissue (31)(32)(33). We found that NOS inhibitor blocked COX-2 expression, and COX-2 inhibitor blocked NOS (iNOS and eNOS) expression in vivo.…”
Section: Discussionmentioning
confidence: 73%